A new species of Lilophaea Bechyné (Coleoptera, Chrysomelidae, Galerucinae) with a historical background and a checklist of the genus - Groll, Elisa Von; Moura, Luciano De A. (Zootaxa, 2016)
A new species of Lilophaea Bechyné (Luperina) from Southern Brazil, Lilophaea sulina sp. nov. is described and illustrated. The complexity behind the taxonomic history for Lilophaea in relation to two similar genera (Luperodes and Monolepta), is approached herein. After the description of L. sulina sp. nov., 19 species of this genus are currently known, all Neotropical. An updated list of species of Lilophaea with their respective geographical distribution is provided.